Experimental investigation on the effect of electron injection into air for thermal decomposition of solid waste. (1st August 2021) - Kobayashi, Yasunori; Ismail, Tamer M.; Kobori, Takahiro; Ding, Lu; Yoshikawa, Kunio; Araki, Kuniomi; Kanazawa, Kiryu; Takahashi, Fumitake
Highlights: The combustion reaction of char was promoted by injecting electrons into air. Carbon oxidation to CO and CO2 was promoted by injecting electrons into air. There is a synergy effect on the thermal decomposition for the mixture. The thermal decomposition of the mixture enhanced by injecting electrons into air. The CH4 production rate increased for the pyrolysis reaction when using electrons. Abstract: In this research, the thermal decomposition characteristics of cellulose, polyethylene, and their mixture with electron injected air were investigated using a laboratory-scale reactor. An electron generator with a voltage of 12 V was adopted as the key part to inject the electrons into the air in order to accelerate the thermal decomposition of the carbonaceous materials in the reactor. In addition, a modified fixed bed reactor was adopted to investigate the effects of the different parameters including the ON/OFF of the electrons injection into air, the thermal decomposition temperatures (400 °C and 500 °C) and the feedstock (cellulose, polyethylene and their mixture) on the syngas generation as well as the weight reduction rate. The results showed that the combustion reaction of char was more accelerated in the electron-ON case than that in the electron-OFF case. For example, in the case of cellulose, the amount of CO2 generation differs about 2 times between the electron ON and OFF cases. Also under the same conditions, the amount of CO generated can be suppressed to about 2/3 by the electron injection. In the case of polyethylene, the electron injection effect was confirmed only for enhancing the CH4 generation. However, there was a significant synergy effect in the electron-ON case for the cellulose and polyethylene mixture. These results showed that the electron injected air can accelerate the combustion reaction of char. The results suggest a potential advantage of electron injection to improve conventional waste incinerators.